Workshop Penguatan Pendidikan Karakter bagi Guru Bimbingan dan Konseling SMP - Akhmad Sugianto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Guidance and Counseling Workshop on Strengthening Character Education in Guidance and Counseling Services for Junior Secondary Guidance and Counseling Teachers in Tabalong Regency was carried out to prepare guidance and counseling teachers who were capable of implementing guidance and counseling services in strengthening character education based on operational guidance and counseling in schools, by the Guidance and Counseling Guidelines for Primary and Secondary Education issued by the Ministry of Education and Culture. The workshop was held one day, namely on August 26, 2019, with 37 participants. Technically, the implementation of the workshop takes place in 5 stages of activities, namely registration; lectures; sharing experiences; and questions and answers practicum. Resource persons for the workshop activities were lecturers in the guidance and counseling study program. Based on the implementation of this service, it can be concluded that guidance and counseling teachers have an essential role in strengthening character education by using guidance and counseling services based on the Operational Guidance and Counseling Implementation Guidelines. Therefore, it is suggested to be followed up into technical guidance activities in implementing guidance and counseling services with a more specific activity agenda; and become a preliminary study in making guidance and counseling service modules for strengthening character education based on Operational Guidance for Guidance and Counseling Implementation.